2015
DOI: 10.11648/j.jps.20150303.17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation of Glutathione S-transferase (GST) in Different Crops and Purification of High Active GSTs from Onion (Allium cepa L.)

Abstract: Glutathione S-transferases (GSTs; EC 2.5.1.18) are abundant proteins encoded by a highly divergent ancient gene family with protective functions through detoxification and non-catalytic roles as carriers of cytotoxins. In this work, we investigated the GST activities in seedlings of 38 crops to obtain a plant with high active GST for further study. In screening of 38 crops, onion seedling showed the highest GST activity (483.54 nmol min -1 mg -1 protein) followed by wheat(372.89 nmol min -1 mg -1 protein), bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Other studies on stress have also found that genes responsible for antioxidants show varying patterns of expression in response to abiotic stressors. OsGPXs are increased in response to drought and oxidative stress, whereas they are downregulated in response to salt, heat, and cold [ 48 ]. It is speculated that this may be due to the abnormal sensitivity of Digitaria sanguinalis to 4,8-DHT, which produces significant quantities of ROS, leading to the inactivation of antioxidant enzymes or its components, exacerbating plant damage.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on stress have also found that genes responsible for antioxidants show varying patterns of expression in response to abiotic stressors. OsGPXs are increased in response to drought and oxidative stress, whereas they are downregulated in response to salt, heat, and cold [ 48 ]. It is speculated that this may be due to the abnormal sensitivity of Digitaria sanguinalis to 4,8-DHT, which produces significant quantities of ROS, leading to the inactivation of antioxidant enzymes or its components, exacerbating plant damage.…”
Section: Discussionmentioning
confidence: 99%
“…Glyoxalase I assay was carried out according to the method of Islam et al (2015) with slight modification. Briefly, the assay mixture contained 100mM sodium phosphate buffer (pH 7.5), 15 mM magnesium sulphate, 1.7 mM glutathione and 3.5 mM MG.…”
Section: Glyoxalase I Assaymentioning
confidence: 99%